2014
DOI: 10.1242/dev.107797
|View full text |Cite
|
Sign up to set email alerts
|

A neuron autonomous role for the familial dysautonomia geneELP1in sympathetic and sensory target tissue innervation

Abstract: Familial dysautonomia (FD) is characterized by severe and progressive sympathetic and sensory neuron loss caused by a highly conserved germline point mutation of the human ELP1/IKBKAP gene. Elp1 is a subunit of the hetero-hexameric transcriptional elongator complex, but how it functions in disease-vulnerable neurons is unknown. Conditional knockout mice were generated to characterize the role of Elp1 in migration, differentiation and survival of migratory neural crest (NC) progenitors that give rise to sympath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
105
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(128 citation statements)
references
References 58 publications
21
105
2
Order By: Relevance
“…It has been postulated that neurons die in FD because of an inability to innervate correctly their targets from which they receive essential survival stimuli in the form of neurotrophins (36,37). We show here that incubation in NGF is insufficient to rescue the small-diameter TrkA + , Ikbkap −/− neurons.…”
Section: Bgp-15 Normalizes Impaired Actin Dynamics In Ikbkapmentioning
confidence: 64%
See 1 more Smart Citation
“…It has been postulated that neurons die in FD because of an inability to innervate correctly their targets from which they receive essential survival stimuli in the form of neurotrophins (36,37). We show here that incubation in NGF is insufficient to rescue the small-diameter TrkA + , Ikbkap −/− neurons.…”
Section: Bgp-15 Normalizes Impaired Actin Dynamics In Ikbkapmentioning
confidence: 64%
“…FD patients have impaired blood pressure regulation and suffer from sudden death resulting from cardiac arrhythmias and asystole (44). These symptoms coincide with a decrease in sympathetic innervation of the heart, particularly its ventral apex (37,45). Based on our finding that BGP-15 could rectify actin dynamics in Ikbkap −/− neurons in vitro, we asked whether treatment with the compound could reverse the defect in cardiac innervation that has previously been reported in Ikbkap −/− embryos (37).…”
Section: Bgp-15 Improves Ikbkapmentioning
confidence: 99%
“…However, we found that FS þ Elp1-TcKO neurons had comparable survival to Elp1-TCtl neurons when 10 ng/mL NGF was present in both CB and DA compartments ( Figure 2C), consistent with our previously published results that used dissociated Elp1-deficient neurons that were completely immersed in NGF. 98 By contrast, when NGF was restricted to distal axons in the DA compartment only 22% of FS þ Elp1-TcKO neurons survived. Elp1-TcKO neurons with 10 ng/mL in the DA compartment survived similar to Elp1-TCtl neurons with 1 ng/mL in the DA compartment; a 10-fold decreased sensitivity in their signaling response to target-derived NGF.…”
Section: Fd: a Model Of Abnormal Retrograde Ngf Signaling Resulting Imentioning
confidence: 99%
“…Thus, sympathetic dysautonomia in FD is likely explained by impairment in retrograde NGF signaling which leads to survival and target tissue innervation abnormalities in the context of limited NGF produced by target tissues. 98 How does Elp1 function in retrograde NGF signaling? Little is currently known about how Elp1 functions in axons, but its role as a component of the transcriptional elongator complex within the nucleus may provide some clues.…”
Section: Fd: a Model Of Abnormal Retrograde Ngf Signaling Resulting Imentioning
confidence: 99%
See 1 more Smart Citation